Trends of Phase I Clinical Trials of New Drugs in Mainland China Over the Past 10 Years (2011–2020) - Chen, Chen; Lou, Ning; Zheng, Xin; Wang, Shasha; Chen, Haizhu; Han, Xiaohong (Frontiers in Medicine, 2021)
Background: In recent years, the number of clinical trials initiated in China has increased rapidly. The aim of this study was to overview the changing landscape of phase I clinical trials in mainland China from 2011 to 2020. Methods: We analyzed phase I clinical trials registered on three websites including the Chinese Clinical Trial Registry, ClinicalTrials.gov, and the China National Medical Products Administration Centre for Drug Evaluation platform. Findings: A total of 2842 phase I clinical trials were posted from Jan 1st, 2011 to December 31st, 2020. Biological drug research increased significantly from 22.6% during 2011-2015 to 33.3% during 2016-2020. These principal investigators (PI) of these clinical trials were mainly from Beijing (n=871), followed by Shanghai (n = 496) and Jiangsu (n = 281). As for the therapeutic area of these phase I clinical trials, cancer took up the most percentage of all clinical trials (35%), followed by infectious disease (9%), nervous system disease (9%), etc. The overall number of clinical trials for innovative drugs was 1497, accounting for half of all phase I clinical trials (53%). Among these 1497 innovative drug clinical trials, 924 were newly tested drugs with an average annual growth rate of 59%. Only a small number of drugs could be made transition to phase II (n=207, 22%). In addition, despite the number of newly tested drugs during 2011-2015 (n=163) was much less than that in 2016-2020 (n=761), the percentage of drugs that could enter into phase II clinical trials in 2011-2015 (34%) was higher than that in 2016-2020 (20%). Conclusion: In the past 10 years, the development of phase I clinical trials has achieved great progress in mainland China due to the novel design and drug innovation policy. Nevertheless, future efforts are needed to make for improving the phase transition success rate of innovative drugs.